Impact of low-frequency electromagnetic fields on DNA instability caused by environmentally and occupationally relevant chemicals in lymphocytes of donors with different demographic characteristics - Miroslav Mišík; Michael Kundi; Franziska Ferk; Hans-Peter Hutter; Armen Nersesyan; Michael Grusch; Siegfried Knasmueller (Archives of Toxicology, 2026)
Aim of this study was to find out if demographic factors (age and body weight) have an impact on the sensitivity of peripheral lymphocytes towards DNA damage caused by extremely low frequency electromagnetic fields (ELF-EMF), to which humans are exposed worldwide. Cells from three different groups (young normal-weight, young obese, and old normal-weight individuals) were treated with different intensities of ELF-EMF (50 Hz, 50, 200 and 1000 µT) in combination with genotoxic agents, which cause damage to the genetic material via different molecular mechanisms. BPDE (benzo[a]pyrene diol epoxide) is a metabolite of the polycyclic aromatic hydrocarbon benzo(a)pyrene (B(a)P); 4-nitroquinoline oxide (4NQO) is a UV-mimetic agent; the metal compounds NiCl 2 and CrO 3 induce cross-links and oxidative damage. The cells were treated with radiation in combination with the different chemicals (simultaneous and sequential exposure), subsequently, DNA damage was monitored using single-cell gel electrophoresis (SCGE) experiments. We found no evidence for induction of genetic damage by the radiation in cells from the different groups. However, a decrease of damage was observed in combined experiments with NiCl 2 , and an increase of DNA migration was detected in some experiments with BPDE. These findings indicate that ELF-EMF does not cause DNA damage in lymphocytes regardless of the age and body weight of the donors. Furthermore, our results show that the radiation has an impact on the extent of DNA damage caused by specific environmentally and occupationally relevant exposures and may increase the genotoxic effects of polycyclic aromatic hydrocarbons.

Effects of school breaks on cognitive performance and mental wellbeing of high school students in indoor and outdoor environments - Arne Arnberger; Renate Eder; Brigitte Allex; Peter Wallner; Lisbeth Weitensfelder; Michael Kundi; Hans-Peter Hutter (Urban Forestry & Urban Greening, 2026)

Impact of high (1950 MHz) and extremely low (50 Hz) frequency electromagnetic fields on DNA damage caused by occupationally relevant exposures in human derived cell lines - Nadine Worel; Miroslav Mišík; Michael Kundi; Franziska Ferk; Hans-Peter Hutter; Armen Nersesyan; Georg Wultsch; Georg Krupitza; Siegfried Knasmueller (Toxicology in Vitro, 2024)

Urban green space preferences for various health-related psychological benefits of adolescent pupils, university students and adults - Arne Arnberger; Renate Eder; Brigitte Allex; Peter Wallner; Lisbeth Weitensfelder; Hans-Peter Hutter (Urban Forestry & Urban Greening, 2024)

Mobile phone specific radiation disturbs cytokinesis and causes cell death but not acute chromosomal damage in buccal cells: Results of a controlled human intervention study - Michael Kundi; Armen Nersesyan; Gernot Schmid; Hans-Peter Hutter; Florian Eibensteiner; Miroslav Mišík; Siegfried Knasmüller (Environmental Research, 2024)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Unexpected air pollutants with potential human health hazards: Nitrification inhibitors, biocides, and persistent organic substances - Johann G. Zaller; Maren Kruse-Plaß; Ulrich Schlechtriemen; Edith Gruber; Maria Peer; Imran Nadeem; Herbert Formayer; Hans-Peter Hutter; Lukas Landler (Science of The Total Environment, 2023)

Red meat, diseases, and healthy alternatives: A critical review - Cem Ekmekcioglu; Peter Wallner; Michael Kundi; Ulli Weisz; Willi Haas; Hans-Peter Hutter (Critical Reviews in Food Science and Nutrition, 2018)

Increased protein synthesis by cells exposed to a 1,800-MHz radio-frequency mobile phone electromagnetic field, detected by proteome profiling - Christopher Gerner; Verena Haudek; Ulla Schandl; Editha Bayer; Nina Gundacker; Hans Peter Hutter; Wilhelm Mosgoeller (International Archives of Occupational and Environmental Health, 2010)